Engagement with women farmers in Akole, Maharashtra, India - Mittra, Sarika; Rana, Jai Chand (Bioversity International and International Center for Tropical Agriculture, 2025)
Group discussion with women farmers participating in on-farm tricot trials from 6 villages in Akole, Maharashtra, India. This report summarizes the key discussions on crops grown during different seasons, seed sourcing, decision-making autonomy, the disposal or sale of produce, and future preferences for agricultural activities.